Fgf8-deficient mice compensate for reduced GnRH neuronal population and exhibit normal testicular function - Zhang, Wei; Johnson, Joshua I.; Tsai, Pei-San (Frontiers in Endocrinology, 2015)
Gonadotropin-releasing hormone (GnRH) is critical for the onset and maintenance of reproduction in vertebrates. The development of GnRH neurons is highly dependent on fibroblast growth factor (Fgf) signaling. Mice with a hypomorphic Fgf8 allele (Fgf8 Het) exhibited a 50% reduction in GnRH neuron number at birth. Female Fgf8 Het mice were fertile but showed significantly delayed puberty. However, it was unclear if these mice suffered additional loss of GnRH neurons after birth, and if male Fgf8 Het mice had normal pubertal transition and testicular function. In this study, we examined postnatal GnRH neuron number and hypothalamic GnRH content in Fgf8 Het mice from birth to 120 days of age. Further, we examined seminal vesicle and testicular growth, testicular histology, and circulating luteinizing hormone (LH) around and after pubertal transition. Our results showed that GnRH neuron numbers were significantly and consistently reduced in Fgf8 Het mice of both sexes in all ages examined, suggesting these animals were born with an inherently defective GnRH system, and no further postnatal loss of GnRH neurons had occurred. Despite an innately compromised GnRH system, male and female Fgf8 mice exhibited normal levels of immunoassayable hypothalamic GnRH peptide at all ages examined except on 60 days of age, suggesting increased GnRH synthesis or reduced turnover as a compensatory mechanism. Fgf8 Het males also had normal seminal vesicle and testicular mass/body mass ratios, testicular histology, and circulating LH. Overall, our data speak to the extraordinary ability of a GnRH system permanently compromised by developmental defect to overcome pre-existing deficiencies to ensure pubertal progression and reproduction.